2021
DOI: 10.1101/2021.09.13.460005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The secrets to domestic bliss – Partner fidelity and environmental filtering preserve stage-specific turtle ant gut symbioses for over 40 million years

Abstract: Background: Gut microbiomes can vary across development, a pattern often found for insects with complete metamorphosis. With varying nutritional need and distinct opportunities for microbial acquisition, questions arise as to how such holometabolous insects retain helpful microbes at larval and adult stages. Ants are an intriguing system for such study. In a number of lineages adults digest only liquid food sources, while larvae digest solid foods. Like some other social insects, workers and soldiers of some a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 185 publications
(291 reference statements)
0
3
0
Order By: Relevance
“…In other social Hymenoptera, larval microbiota also differ from those of adults. For example, in Cephalotes turtle ants, larval microbiota can change substantially over the course of development (Hu et al, 2021), exhibiting a consistent successional pattern of unknown functional importance. Bacteria can play important roles in larvae of other social Hymenoptera.…”
Section: Discussionmentioning
confidence: 99%
“…In other social Hymenoptera, larval microbiota also differ from those of adults. For example, in Cephalotes turtle ants, larval microbiota can change substantially over the course of development (Hu et al, 2021), exhibiting a consistent successional pattern of unknown functional importance. Bacteria can play important roles in larvae of other social Hymenoptera.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the microbiome of eusocial insect queens are not as frequent as those on worker castes, despite the key role of the queen for superorganism fitness. However, studies conducted so far have revealed that the microbiome of queens—including species of termites, ants, and bees—usually differs from that of their workers ( 28 , 34 , 35 ). The lack of direct correlation between worker and queen microbiomes reinforces the importance of queen microbiome characterization to understand colony-level microbiome assembly, functional roles, and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the microbiome of eusocial insect queens are not as frequent as those on worker castes, despite the key role of the queen for superorganism fitness. However, studies conducted so far have revealed that the microbiome of queens – including species of termites, ants and bees – usually differs from that of their workers (23, 29, 30). The lack of direct correlation between worker and queen microbiomes reinforces the importance of queen microbiome characterization to understand colony-level microbiome assembly, functional roles and evolution.…”
Section: Discussionmentioning
confidence: 99%